Butene Emissions From Coastal Ecosystems May Contribute to New Particle Formation. Issue 10 (20th May 2022) - Giorio, Chiara; Doussin, Jean‐François; D'Anna, Barbara; Mas, Sébastien; Filippi, Daniele; Denjean, Cyrielle; Mallet, Marc Daniel; Bourrianne, Thierry; Burnet, Frédéric; Cazaunau, Mathieu; Chikwililwa, Chibo; Desboeufs, Karine; et al.
Abstract: Marine ecosystems are important drivers of the global climate system. They emit volatile species into the atmosphere, involved in complex reaction cycles that influence the lifetime of greenhouse gases. Sea spray and marine biogenic aerosols affect Earth's climate by scattering solar radiation and controlling cloud microphysical properties. Here we show larger than expected marine biogenic emissions of butenes, three orders of magnitude higher than dimethyl sulfide, produced by the coastal part of the Benguela upwelling system, one of the most productive marine ecosystems in the world. We show that these emissions may contribute to new particle formation in the atmosphere within the marine boundary layer through production of Criegee intermediates that oxidize SO2 to H2 SO4 . Butene emissions from the marine biota may affect air quality and climate through ozone, secondary organic aerosol, and cloud condensation nuclei formation even in pristine regions of the world. Our results indicate a potentially important role of butene emissions in marine particle formation that requires investigation in other regions. Plain Language Summary: Marine biogenic emissions of volatile organic compounds (VOCs) are key drivers of the Earth's climatic system, but they are not considered in climate models, except for dimethyl sulfide (DMS). We observed massive concentrations of reactive VOCs, especially butenes, in ambient air at a pristine coastal site on the west coast of the southern African continent. These strong emissions originated from the coastal part of the Benguela ecosystem and may have contributed to new particle formation in the marine boundary layer. According to our observations, butenes can be found at concentrations orders of magnitude larger than DMS in highly productive coastal environments and thus their climatic impact requires investigation. Key Points: Marine biogenic emissions of reactive volatile organic compounds previously thought to be anthropogenic Massive emissions of butenes from the coastal part of the Benguela upwelling system Emissions of butenes may contribute to new particle formation in the marine boundary layer